2008
DOI: 10.1161/strokeaha.107.509695
|View full text |Cite
|
Sign up to set email alerts
|

Mortality Rates for Stroke in England From 1979 to 2004

Abstract: Background and Purpose-Stroke mortality appears to be declining more rapidly in the UK than in many other Western countries. To understand this apparent decline better, we studied trends in mortality in the UK using more detailed data than are routinely available. Methods-Analysis of datasets that include both the underlying cause and all other mentioned causes of death (together, termed "all mentions"): the Oxford Record Linkage Study from 1979 to 2004 and English national data from 1996 to 2004. Results-Mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
29
2
1

Year Published

2008
2008
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 40 publications
5
29
2
1
Order By: Relevance
“…10,12 Changes over time in certification practices by physicians are another area of concern, although they are unlikely to explain the observed decline in stroke mortality. 13 Moreover, similar rates of mortality decline have been observed in epidemiological studies with standardized ascertainment of stroke cases within registration areas. 14 Our results for 7 western European countries cannot be generalized to other regions of the world.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…10,12 Changes over time in certification practices by physicians are another area of concern, although they are unlikely to explain the observed decline in stroke mortality. 13 Moreover, similar rates of mortality decline have been observed in epidemiological studies with standardized ascertainment of stroke cases within registration areas. 14 Our results for 7 western European countries cannot be generalized to other regions of the world.…”
Section: Discussionsupporting
confidence: 57%
“…4 On the other hand, in the United States, stroke mortality has declined over recent decades with approximately 0.3% to 2.9% per year, 16 suggesting similar rates of decline as in western Europe. [11][12][13] Acknowledged demographers, Wilmoth 7 and Oepen and Vaupel, 17 argue that future trends in mortality can best depart from extrapolations of past trends in mortality as observed over a longer period. We therefore based our projections on the declines in stroke mortality as observed in the 7 European countries over a 25-year period.…”
Section: Discussionmentioning
confidence: 99%
“…The author also reports that, considering all causes of death in Brazil, CVA has become the main one, bypassing coronary heart disease. The reduction in CVA mortality began in the mid-1960s and was stabilized at the end of the twentieth century [21][22][23][24] . This decline was more pronounced in the United States, Canada, Australia, the Western Europe countries and Japan [23][24][25][26] , whereas the rates are higher in South America and Eastern Europe and still increasing in Eastern Europe countries [23][24][25][26][27] .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the 55% reduction in mortality that has occurred in our own population-based study is comparable to the reduction in mortality reported by the Oxford Linkages study in an analysis of routinely collected data within the wider Oxfordshire population over a similar time period. 40 A further source of bias in analyzing time trends in SAH outcome is the improvement in availability and quality of brain imaging, which has reduced misdiagnosis of SAH and probably improved the detection of milder cases in later study periods. We have tried to minimize this source of bias by limiting our analysis to studies in which the proportion of stroke classified by brain imaging or postmortem was Ͼ80% throughout the study.…”
Section: Figurementioning
confidence: 99%